OPTIMIZATION OF BISULFIT SALT CONCENTRATION ON COCONUT QUALITY CONTROL OF COCONUT - Ellya Indahyanti; Budi Kamulyan; Bambang Ismuyanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
Bisulphite salt is an additive that usualy added into foodstuff, it was used in order to take a preservation effects. In this research, it was added into coconut sap. The aim of this research was to study the effects of sodium bisulphite adding for increasing coconut sap quality, including pH, reducing sugar and sucrose content. In addition, the rate of sucrose hydrolysis with and without bisulphite have been compared. The volumetric method, i.e Lane-Eynon procedure was used for determining the sugar contents while the hydrolysis rates were measured by polarimetry. The results showed that bisulphite added into coconut sap could repress sucrose hydrolysis.